ANALISIS KESALAHAN SIMPLE PRESENT TENSE DAN PRESENT CONTINUOUS TENSE: STUDI KASUS DI SEMINARI ST. FRANSISKUS XAVERIUS TOMOHON - Gaspersz, Andrey Abrian; Warouw, Maya P.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â  This research, entitledÂ  â€œError Analysis of Simple Present Tense and Present Continuous Tense: A Case Study at Seminary of St. Francis Xavier Tomohonâ€. Â This research is an attempt to identify, classify, and analyze the kind of errors made by the first year students of Seminary St. Francis Xavier Tomohon when using the simple present tense and present continuous tense in writing English. This research used a case study approach. The data were taken from the first year students in seminary by making a test about simple present tense and present continuous tense and giving a topic for the students to make an essay. The writer uses some techniques of analyzing the data, as follows: identification of error, classification, description, and correction. The result of this research shows that there are four types of errors made by the students.Â  Those errors are omission, misinformation, misordering, and addition. Based on this errors, the writer also finds some forms of errors. The writer finds the error of verb omission (-es, -s), auxiliary omission of the negative sentence, omission of to be, omission of â€“ing form, misinformation of simple present tenseâ€™sÂ  verb, misinformation of to be, misinformation of present continuos tenseâ€™s verb, misordering of the subject, misordering of the object, misordering of adverb, misordering of conjunction, addition of simple present tenseâ€™s verb, addition of preposition, addition of â€“ing, addition of to be, and addition of verbâ€™s base form. Â Key words: Error Analysis, Simple Present Tense, Present Continuos Tense, Studentsâ€™ Essays